2013
DOI: 10.1177/1473871613500978
|View full text |Cite
|
Sign up to set email alerts
|

Performance and interaction behaviour during visual search on large, high-resolution displays

Abstract: Large, high-resolution displays (LHRDs) allow orders of magnitude more data to be visualized at a time than ordinary computer displays. Previous research is inconclusive about the circumstances under which LHRDs are beneficial and lacks behavioural data to explain inconsistencies in the findings. We conducted an experiment in which participants searched maps for densely or sparsely distributed targets, using 2 million pixel (0.4m × 0.3m), 12 million pixel (1.3m × 0.7m) and 54 million pixel displays (3.0m × 1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Wall-sized displays are well-suited to small groups of users working together on large amounts of data: Multiple users can move freely in front of the display to get an overview or see details without changing its content [2], leading to a variety of collaboration styles [11]. Previous work has demonstrated the benefits of such displays in various tasks including sensemaking [1], way-finding [17], searching [22] and exploratory visual analysis [21]. Liu et al [13] showed the performance advantage, as the amount of data increases, of using a ultra-high resolution wall-sized display vs. a classical desktop setup for a single-user classification task.…”
Section: Introductionmentioning
confidence: 99%
“…Wall-sized displays are well-suited to small groups of users working together on large amounts of data: Multiple users can move freely in front of the display to get an overview or see details without changing its content [2], leading to a variety of collaboration styles [11]. Previous work has demonstrated the benefits of such displays in various tasks including sensemaking [1], way-finding [17], searching [22] and exploratory visual analysis [21]. Liu et al [13] showed the performance advantage, as the amount of data increases, of using a ultra-high resolution wall-sized display vs. a classical desktop setup for a single-user classification task.…”
Section: Introductionmentioning
confidence: 99%
“…However, performance varies according to the nature of the task being undertaken; while beneficial for searching for specific objects in an image, too much detail can be distracting for tasks that involve pattern finding [9]. Previously, we conducted an experiment in which participants searched for targets which were either densely distributed (requiring an exhaustive search) or were sparsely distributed [11]. We found that display resolution does not affect the speed at which densely distributed targets are found but results in a significant improvement when searching for sparsely distributed targets in easily identifiable regions of interest (ROIs).…”
Section: Introductionmentioning
confidence: 99%
“…Trellises [8], [9] reduce the cost because multiple projections of the data are visible at one time, which clearly benefits comparative plotting (R6). Ultra-high-definition displays are likely to provide further benefits by reducing the amount of panning and zooming that users need to perform [28].…”
Section: State-change Costs To Evaluate Interpretationmentioning
confidence: 99%